2019
DOI: 10.1007/s40684-019-00038-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Thermal-Related Effects in Hot SPIF of Ti–6Al–4V Alloy

Abstract: Two relevant references of the IJPEM journal have been included in the final version (ref. 2 and ref. 24). Regarding the JPGT, a relevant paper related to the topic of the present manuscript had already been included (ref. 11).•The box frame of several figures has been removed.Yours Sincerely,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…First, the preliminary trials have served to define the optimal working temperature (675 • C) using the current set-up. In this sense, the results have shown that, in general, within the analyzed range, a temperature increase had an overall positive effect since the positive underforming deviations that were mainly related to the springback effect decreased, in agreement with other studies [4][5][6][7]. However, this fact was not enough to obtain sufficiently accurate Ti-6Al-4V parts.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…First, the preliminary trials have served to define the optimal working temperature (675 • C) using the current set-up. In this sense, the results have shown that, in general, within the analyzed range, a temperature increase had an overall positive effect since the positive underforming deviations that were mainly related to the springback effect decreased, in agreement with other studies [4][5][6][7]. However, this fact was not enough to obtain sufficiently accurate Ti-6Al-4V parts.…”
supporting
confidence: 87%
“…Both heating devices, one in the oven cavity and the other one around the clamping, are governed by a Programmable Logic Controller (PLC) through two pyrometers (thermocouples for the fiber blanket cover) that continuously read the sheet temperature at the center and the area close to the clamping. A backing plate below the flange zone ( Figure 3) was used to reduce the deflection observed in the area in previous experimentation [4]. The trials were performed on an in-house 5-axis gantry machine equipped with a furnace, a sheet clamping device, and a housed head that protects it against temperature increase ( Figure 2).…”
Section: Experimental Set Upmentioning
confidence: 99%
See 3 more Smart Citations